TV Consumption Patterns and the Impact of Media Freedom on Political Trust and Satisfaction with the Government - Bodo Knoll; Hans Pitlik; Martin Rode (Social Indicators Research, 2023)
This paper empirically assesses the impact of media freedom on citizen's trust in politicians and satisfaction with national governments. Restrictions potentially allow governments to provide citizens with biased information, which may then increase trust in, and satisfaction with, ruling elites. Yet, these restrictions may also be perceived as a signal that the latter are not trustworthy. Employing data from the European Social Survey to compare respondents with different levels of media consumption, we show that unfree media are partially effective in manipulating perceptions. Using age as an instrument for the time dedicated to media consumption, we find that higher levels of media freedom reduce citizen's trust in government but are unrelated to satisfaction with national governments.
Keywords: D72; D83; H80; 300; Political trust; Government satisfaction; Media freedom; TV consumption